Sterile inflammation as a factor in human male infertility: Involvement of Toll like receptor 2, biglycan and peritubular cells - Mayer C; Adam M; Glashauser L; Dietrich K; Schwarzer JU; Kohn FM; Strauss L; Welter H; Poutanen M; Mayerhofer A (NATURE PUBLISHING GROUP, 2025)
Changes in the wall of seminiferous tubules in men with impaired spermatogenesis imply sterile inflammation of the testis. We tested the hypothesis that the cells forming the wall of seminiferous tubules, human testicular peritubular cells (HTPCs), orchestrate inflammatory events and that Toll like receptors (TLRs) and danger signals from the extracellular matrix (ECM) of this wall are involved. In cultured HTPCs we detected TLRs, including TLR2. A TLR-2 ligand (PAM) augmented interleukin 6 (IL-6), monocyte chemo-attractant protein-1 (MCP-1) and pentraxin 3 (PTX3) in HTPCs. The ECM-derived proteoglycan biglycan (BGN) is secreted by HTPCs and may be a TLR2-ligand at HTPCs. In support, recombinant human BGN increased PTX3, MCP-1 and IL-6 in HTPCs. Variable endogenous BGN levels in HTPCs derived from different men and differences in BGN levels in the tubular wall in infertile men were observed. In testes of a systemic mouse model for male infertility, testicular sterile inflammation and elevated estradiol (E2) levels, BGN was also elevated. Hence we studied the role of E2 in HTPCs and observed that E2 elevated the levels of BGN. The anti-estrogen ICI 182,780 blocked this action. We conclude that TLR2 and BGN contribute to sterile inflammation and infertility in man.